Antimicrobial Efficiency of Chitosan Solutions and Coatings Incorporated with Clove Oil and/or Ethylenediaminetetraacetate. Issue 4 (12th September 2014) - He, Shoukui; Yang, Qiaomu; Ren, Xiaoyun; Zi, Jiahui; Lu, Saisai; Wang, Shuqi; Zhang, Yunbin; Wang, Yifei
Abstract Bioactive edible coatings based on chitosan (Ch) were developed by incorporating clove oil (CO) and/or ethylenediaminetetraacetate (E), with the aim of promoting the microbial quality of meat. The antimicrobial mode of Ch‐based coatings was also explored in terms of membrane permeability. Results showed that the addition of CO and/or E provoked a significant (P < 0.05) increase in diameter of inhibition zones. In the growth inhibition assay, Ch + CO + E solution exhibited the highest inhibition rates of Escherichia coli and Staphylococcus aureus (99.17 and 96.42%, respectively). A pork slice coating test showed that CO and/or E incorporated coatings could moderate the growth of total microbes and maintain acceptable sensory characteristics of pork in 7 days of storage at 4C. The coatings of Ch, Ch + CO and Ch + CO + E improved both lightness and red color stability of pork. Furthermore, four kinds of coating solutions induced the release of intracellular components, indicating the damage of cell membranes. This study suggests the potential utilization of Ch + CO and Ch + CO + E coatings for antimicrobial purposes in refrigerated pork. Practical Applications Increasing demands for food quality and safety have boosted the development of bioactive edible coatings and films to maintain quality attributes of food products in recent years. Edible coatings based on polysaccharides have shown great promise. Microbial growth on the food surface is a principal cause of food spoilage. Hence, the antimicrobial efficiency of edible coatings is of prime importance. In this study, clove oil (CO) and ethylenediaminetetraacetate (E) were incorporated into chitosan (Ch) coating to improve its antimicrobial activity. Results from in vitro and in vivo tests demonstrated that Ch + CO and Ch + CO + E coatings could be utilized as active packaging materials for refrigerated pork.